2012
DOI: 10.1007/s10750-012-1136-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in-stream macroinvertebrate communities following a severe fire in the Lake Tahoe basin, California

Abstract: Large and severe wildfires can dramatically alter terrestrial and aquatic ecosystems. We documented changes in benthic macroinvertebrate communities and physical habitat at two sites along Angora Creek, CA, USA for 2 years following a severe fire. Although post-fire years had low precipitation, canopy cover and bank stability declined dramatically following the wildfire (canopy cover: 88% pre-fire, 22% post-fire; stable bank: 93% pre-fire, 11% post-fire). Substrate also changed substantially, with fine sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…As such, it will be important to protect permanent sources of surface water from disturbance (both natural and anthropogenic) in the future to minimise the impacts of drought on freshwater crayfish Robson 2011, 2013 Verkaik et al 2014). Minshall (2003) suggested that intense fires will have larger effects on stream fauna, which has been corroborated by findings following an intense fire in California (Oliver et al 2012) and another in central Victoria, Australia (Verkaik et al 2014). In contrast, some authors suggest that wetland invertebrates cope well with a variety of stresses (Beganyi and Batzer 2011) and may show little response to fire compared to stream communities (Minshall 2003).…”
Section: Wildfire and Droughtmentioning
confidence: 92%
See 2 more Smart Citations
“…As such, it will be important to protect permanent sources of surface water from disturbance (both natural and anthropogenic) in the future to minimise the impacts of drought on freshwater crayfish Robson 2011, 2013 Verkaik et al 2014). Minshall (2003) suggested that intense fires will have larger effects on stream fauna, which has been corroborated by findings following an intense fire in California (Oliver et al 2012) and another in central Victoria, Australia (Verkaik et al 2014). In contrast, some authors suggest that wetland invertebrates cope well with a variety of stresses (Beganyi and Batzer 2011) and may show little response to fire compared to stream communities (Minshall 2003).…”
Section: Wildfire and Droughtmentioning
confidence: 92%
“…The sediment layer had the effect of reducing habitat heterogeneity by burying boulders, cobbles and woody debris, simplifying habitats and reducing water depth (especially in the case of stream pools which filled with ash and sediment), thereby also reducing habitat area (Figure 2). An increase in fine sediment is a common finding in studies examining fire effects on aquatic ecosystems (Oliver et al 2012;Verkaik et al 2014). Such sediment may also be washed downstream where it may also affect unburnt reaches (Lane et al 2006;Peat et al 2005;Oliver et al 2012).…”
Section: Wildfire and Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our prediction of higher prevalence of scrapers on water-than on soil-conditioned wood was not supported. We based our prediction on the expectation that periphyton growth would be greater on water-than on soil-conditioned wood (Oliver et al 2012), but the conditioning period might have been too short for us to detect a response Webster 1988, Hall et al 2001).…”
Section: Trait Responsesmentioning
confidence: 99%
“…Several investigators have examined the effects of wildfire on stream macroinvertebrates (Minshall et al 1997, Minshall 2003, Vieira et al 2004, Robinson et al 2005, Malison and Baxter 2010, Oliver et al 2012), but none addressed the role of fire-derived wood in stream function. Knowledge regarding interactions between macroinvertebrates and allochthonous inputs is based mainly on leaflitter studies (Wallace et al 1997, Gessner et al 1999, Graça 2001, Gulis et al 2006, Casas et al 2011), but leaf and wood decomposition differ greatly (e.g., Hax and Golladay 1993).…”
mentioning
confidence: 99%